Improving sensory integration in Chinese children with moderate sensory integration challenges through engaging basketball training - Ge, Sha; Guo, Xuepeng; Jiang, Bo Y.; Cordova, Alberto; Guan, Jianmin; Zhang, John Q.; Yao, Wan X. (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to evaluate the effectiveness of combining basketball training with a traditional sensory integration therapy (SIT) vs. a SIT alone in enhancing sensory integration capability among Chinese children diagnosed with mild challenges in sensory integration and sensory processing (CSISP).MethodsThis study comprised a Control group and an Experimental group, both undergoing a 10-week intervention (4 sessions/week, 45 min/session). The Control group exclusively participated in traditional SIT for all sessions. In contrast, the Experimental group engaged in traditional SIT for two sessions per week and Basketball training for the remaining two sessions weekly. Three sensory integration measures (vestibular sensation, tactile perception, proprioception) and five gross motor performance measures (balance beam walking speed, single-leg standing with eyes closed, tennis ball throw, two-legged jump speed, 10-m shuttle run) were assessed before and after the 10-week training period. Separate 2 (Group) × 2 (Test Phases) Analysis of Variance (ANOVA) with repeated measures on the second factor were conducted for each measure. Interaction effects were further explored using Tukey's HSD test to clarify their nature.ResultsBoth groups demonstrated significant improvements in all sensory integration and gross motor performance measures following the 10-week training sessions (p < 0.001). Importantly, the group receiving the combination of basketball training and traditional SIT significantly outperformed the group undergoing SIT alone in all assessed areas.ConclusionThese results indicate that combining basketball training with traditional SIT enhances sensory integration capabilities more effectively among Chinese children aged 4–6 years with moderate CSISP compared to utilizing SIT alone.